Promoting Development in Shared River Basins : Case Studies from International Experience - Altingoz, Mehmet; Belinskij, Antti; Bréthaut, Christian; do Ó, Afonso; Gevinian, Suren; Hearns, Glen; Keskinen, Marko; McCracken, Melissa; Ni, Vadim; Solninen, Niko; Wolf, Aaron T. (World Bank, Washington, DC, 2018)
Transboundary freshwater systems create inevitable linkages and interdependencies between countries. The use of shared water resources by one country will, in most cases, impact other countries sharing the same system. At the same time, coordination among countries in the development of transboundary basins can yield greater benefits than would be available to individual countries pursuing individual development. UN Sustainable Development Goal 6 Target 5 recognizes this potential, calling on the world community to implement integrated water resources management at all levels, ‘including through transboundary cooperation as appropriate’. With a growing number of basins in which water use and demand permanently or temporarily exceeds the amount of renewable water available, and uncertainty from climate change, SDG Target 6.5 becomes increasingly relevant to development interventions designed to secure availability of supplies and create resilience.